To What Extent Is a Highly Successful Men’s NCAA Division II Cross Country Coach Humanistic? A Case Study - Jenny, Seth E. (Journal of Intercollegiate Sport, 2017)
The purpose of this case study was to investigate the coaching philosophy of a highly successful men’s United States National Collegiate Athletic Association (NCAA) division II cross country coach and determine to what extent his stated philosophy and actual coaching methods were humanistic. For the past 13 seasons, the participant coach’s men’s cross country team has finished either first or second at the NCAA division II national championships. In-depth semistructured qualitative interviews of the participant coach and three of his athletes were conducted in addition to eight overt naturalistic training session observations. All data were triangulated to generate themes to determine if the stated coaching philosophy and actual methods were congruent with the humanistic philosophy. The findings indicated that the coach was for the most part humanistic in regards to individualization, but was not humanistic in relation to open communication and collaborative decision-making with athletes, or a process-orientated definition of success. Implications of these findings include what may be the most effective coaching philosophy for men’s NCAA division II cross country running through examining a highly successful coach in the discipline.